DESIGN OF ELECTRICAL POWER DISTRIBUTION SYSTEM IN A PETROCHEMICAL STORAGE FACILITY - ABD WAHAB, NORA AFZAM (Universiti Teknologi Petronas, 2006)
The project title, "Design of Electrical Power Distribution System in A Petrochemical Storage Facility", is basically an idea to have a design study on how the power distribution system is constructed for the industrial plant. This project will start from the basic knowledge, study the related field, estimating and calculating the main elements required for the design. The project is started by analysis towards the previous practice or existing network of any power distribution system. This project will focus on the power flow analysis, short circuit analysis and the procedure of designing the network elements. The network elements for electrical distribution can be transformer, conductor, protection device and others. Throughout the design procedure, the study on how the power flow and short circuit is done to give benefit for the student to learn, besides giving an idea and clear view to the student on how the overcurrent protective device, the conductors, the transformer rating, load demand and other elements are being sized and connected in a network.